Muscle LIM Protein: Master regulator of cardiac and skeletal muscle functions - Vafiadaki, E.; Arvanitis, DA; Sanoudou, D. (GeneGeneGene, 2015)
Muscle LIM Protein (MLP) has emerged as a key regulator of striated muscle physiology and pathophysiology. Mutations in cysteine and glycine-rich protein 3 (CSRP3), the gene encoding MLP, are causative of human cardiomyopathies, whereas altered expression patterns are observed in human failing heart and skeletal myopathies. In vitro and in vivo evidences reveal a complex and diverse functional role of MLP in striated muscle, which is determined by its multiple interacting partners and subcellular distribution. Experimental evidence suggests that MLP is implicated in both myogenic differentiation and myocyte cytoarchitecture, although the full spectrum of its intracellular roles still unfolds.
Vafiadaki, ElizabethArvanitis, Demetrios ASanoudou, DespinaengU54 GM114833/GM/NIGMS NIH HHS/GM114833/GM/NIGMS NIH HHS/R01 GM089820/GM/NIGMS NIH HHS/R01 GM083924/GM/NIGMS NIH HHS/GM089820/GM/NIGMS NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov'tReviewNetherlands2015/05/06 06:00Gene. 2015 Jul 15;566(1):1-7. doi: 10.1016/j.gene.2015.04.077. Epub 2015 Apr 30.
Keywords: Animals; Heart Diseases/physiopathology; Humans; LIM-Homeodomain Proteins/chemistry/genetics/*physiology; Muscle Proteins/chemistry/genetics/*physiology; Muscles/*physiology; Muscular Diseases/physiopathology; Protein Structure, Tertiary